Ethnobotany of Montseny biosphere reserve (Catalonia, Iberian Peninsula): plants used in veterinary medicine. - Bonet, M. Angels; Vallès, Joan (Journal of ethnopharmacology, 2007)
The present paper deals with plants used in veterinary medicine in Montseny. An ethnobotanical survey was carried out in the Montseny massif, which is situated in north-east Catalonia (Iberian Peninsula), covers 826 km(2) and has a population of 80,000. The information was obtained through 120 ethnobotanical interviews to 180 informants. Out of 584 species reported, 351 are claimed to be used in the health field (human and veterinary medicine), 280 in human and animal food and 236 have another kind of popular use. Medicinal species represent around 16.5% of Montseny's vascular flora. In a previous paper we addressed plant use in human medicine, and the present paper deals with veterinarian uses. As a reflection of the importance of rural life in the region, at least until recent times, a substantial number of medicinal plants (89 species, representing 6% of the flora of the territory and 6.4% of all medicinal use-reports in the region) is used in veterinary medicine. These remedies are mostly for cows, calves, sheep, pigs and horses, and secondarily, to poultry, rabbits and dogs. The main ailments treated are postnatal problems, intestinal troubles, wounds and dermatological problems. In many cases, the use of these remedies in veterinary medicine is fully consistent with their use in human medicine.
The following values have no corresponding Zotero field: accession-num: 17059874
Keywords: Catalonia; Ethnobotany; Ethnoveterinary; Medicinal plants; montseny; Traditional knowledge

Ethnobotany of Montseny biosphere reserve (Catalonia, Iberian Peninsula): plants used in veterinary medicine. - Bonet, M Angels; Vallès, Joan (Journal of ethnopharmacology, 2007)
The present paper deals with plants used in veterinary medicine in Montseny. An ethnobotanical survey was carried out in the Montseny massif, which is situated in north-east Catalonia (Iberian Peninsula), covers 826 km(2) and has a population of 80,000. The information was obtained through 120 ethnobotanical interviews to 180 informants. Out of 584 species reported, 351 are claimed to be used in the health field (human and veterinary medicine), 280 in human and animal food and 236 have another kind of popular use. Medicinal species represent around 16.5% of Montseny's vascular flora. In a previous paper we addressed plant use in human medicine, and the present paper deals with veterinarian uses. As a reflection of the importance of rural life in the region, at least until recent times, a substantial number of medicinal plants (89 species, representing 6% of the flora of the territory and 6.4% of all medicinal use-reports in the region) is used in veterinary medicine. These remedies are mostly for cows, calves, sheep, pigs and horses, and secondarily, to poultry, rabbits and dogs. The main ailments treated are postnatal problems, intestinal troubles, wounds and dermatological problems. In many cases, the use of these remedies in veterinary medicine is fully consistent with their use in human medicine.
Keywords: Catalonia; Ethnobotany; Ethnoveterinary; Medicinal plants; montseny; Traditional knowledge

Líquenes y hongos liquenícolas epífitos de Quercus ilex L., poco conocidos en encinares de Cataluña (España) - Longán, Angels; Gómez-Bolea, Antonio; Biologia, Dep; Unitat, Vegetal; Biologia, Fac; Barcelona, Unív (Cryptogamie Mycologie, 1999)
We present here 13 species of lichens and 3 of lichenicolous fungi found on Quercus ilex L. in evergreen oak forests of Catalonia. Leptogium coralloideum (Meyen & Flotow) Vainio, Scoliciosporum gallurae Vězda & Poelt, Abrothallus microspermus Tul. are new reports for Spain, and nine more species are new for the flora of Catalonia. For each one of them, a brief morphological characterisation, its distribution in Europe and in the Iberian Peninsula, and its autoecology are given.
Keywords: Catalonia; epiphytes; lichens; Quercus ilex

Líquenes y hongos liquenícolas epífitos de Quercus ilex L., poco conocidos en encinares de Cataluña (España) - Longán, Angels; Gómez-Bolea, Antonio; Biologia, Dep; Unitat, Vegetal; Biologia, Fac; Barcelona, Unív (Cryptogamie Mycologie, 1999)
We present here 13 species of lichens and 3 of lichenicolous fungi found on Quercus ilex L. in evergreen oak forests of Catalonia. Leptogium coralloideum (Meyen & Flotow) Vainio, Scoliciosporum gallurae Vězda & Poelt, Abrothallus microspermus Tul. are new reports for Spain, and nine more species are new for the flora of Catalonia. For each one of them, a brief morphological characterisation, its distribution in Europe and in the Iberian Peninsula, and its autoecology are given.
Keywords: Catalonia; epiphytes; lichens; Quercus ilex

Studies on pharmaceutical ethnobotany in the regions of L'Alt Empordà and Les Guilleries (Catalonia, Iberian Peninsula). - Bonet, M a; Parada, M; Selga, A; Vallès, J (Journal of ethnopharmacology, 1999)
An ethnobotanical survey was carried out in two regions (L'Alt Emporda and Les Guilleries), situated in North East Catalonia (Iberian Peninsula), with an approximate area of 800 km2 and a population of 68000. Through interviews with 73 people, data was obtained on the medicinal uses of 220 species. The most important findings are presented here concerning the ethnopharmacology of those areas. One hundred and ninty four unreported or uncommon uses corresponding to 101 plant species were detected.
Keywords: Catalonia; Ethnobotany; Folk medicine; Medicinal plants; Quantitative ethnobotany

Contribution to the knowledge of the pharmaceutical ethnobotany of La Segarra region (Catalonia, Iberian Peninsula). - Raja, D; Blanché, C; Vallès Xirau, J (Journal of ethnopharmacology, 1997)
An ethnobotanical survey was carried out in the region known as La Segarra, situated at the north east of the Iberian Peninsula, in the inner plains of Catalonia, with an area of 720 km2 and a population of 17000. Working with 29 people, data on uses of 142 species belonging to 54 botanical families were obtained and presented, of which 13 uses corresponding to nine plant species were previously unreported.
Keywords: Catalonia; Ethnobotany; Folk medicine; Medicinal plants